Air pollution assessment using intuitionistic hierarchical fuzzy inference systems - Olej, Vladimír; Hájek, Petr (Univerzita Pardubice, 2009)
The paper presents the basic notions of intuitionistic fuzzy sets and intuitionistic fuzzy inference systems. Further, there is a design of intuitionistic hierarchical fuzzy inference system of Mamdani type for air pollution assessment. The proposed approach is based on the fact that air pollution assessment is rather subjective. Therefore, a generalization of fuzzy logic seems to be suitable for air pollution assessment.
Keywords: air pollution; air quality; intuitionistic fuzzy logic; intuitionistic fuzzy inference systems